PKM Literatur Keuangan dalam Pengenalan Aplikasi Pinjaman Online terhadap Mahasiswa Universitas Sampoerna (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2023)
The increasingly diverse level of community needs for fulfilling the basics of life is one of the psychological impacts following the passing of the Covid 19 pandemic in 2021. As for restrictions on mobilization, digitalization has also developed, which over time has become a lifestyle whose benefits are now starting to be felt. One of them is easy access to various digital platforms for daily needs such as shopping, education, investment, payments, loans, and so on. So that consumers and the public are wise in managing their finances to meet appropriate economic standards. These economic standards are based on the importance of understanding financial literacy in effective management. Based on data from the Financial Services Authority (OJK), the total number of online   loan distributors from Fintech Lending in Indonesia will reach IDR 225.55 trillion in 2022. This number is up 44.6% compared to the previous year which was IDR 155.97 trillion. The presence of the fintech industry in offering digital-based financial products seems to open new doors for people who want to apply for loans. In contrast to conventional loan services offered by banks or cooperatives, various fintechs offer peer to peer lending (p2p lending) or online   loan products that can be applied for very easily and without complicated requirements. Because of the ease and speed of response, online   loan applications have become very popular among the younger generation and are predicted to continue to grow. Because of this, financial literacy is considered important for Sampoerna University students amidst low understanding of financial literature and the development of online   loan applications. Making wise decisions is also a concern when the risk occurs so that consumers and society are able to face all existing responsibilities. Risk management is basic knowledge in every decision making process. So it is hoped that students as consumers/borrowers will have the knowledge and ability to manage finances appropriately and effectively. Abstracts in Indonesian are written using TNM 10. The distance between lines is 1 space. The abstract contains 150-250 words and only consists of 1 paragraph, which contains objectives, methods, objects/partners, tools and materials, as well as research results.